How do dancers learn to dance?: a first-person perspective of dance acquisition by expert contemporary dancers - Rivière, P. J.; Alaoui, F. S.; Caramiaux, B.; Mackay, E. W. (Proceedings of the 5th International Conference on Movement and Computing, 2018)
We are interested in supporting motor skill acquisition in highly creative skilled practices such as dance. We conducted semi-structured interviews with 11 professional dancers to better understand how they learn new dance movements. We found that each dancer engages in a set of operations, including imitation, segmentation, marking, or applying movement variations. We also found a progression in learning dance movements composed of three steps consistently reported by dancers: analysis, integration and personalization. In this study, we aim to provide an empirical foundation to better understand the acquisition of dance movements from the perspective of the learner.